2011 Triennial Surveillance Review and Review of the 2007 Decision : Concept. (Policy Papers; Policy Paper, 2011)
Over the past three years, the IMF has worked to assist members in addressing the repercussions of the global financial crisis while also tackling gaps in its surveillance framework that the crisis laid bare. This reform agenda has drawn extensively from the recommendations of the 2008 Triennial Surveillance Review (TSR), as well as subsequent IMF and IEO reviews of the Fund's performance in the run-up to the crisis. This TSR provides an opportunity to take stock of the steps taken and to assess recent experience with surveillance.